1985
DOI: 10.1007/bf02388763
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of small sequestra by computerized tomography

Abstract: The diagnosis of osteomyelitis is usually clear by a constellation of clinical, radiographic, and/or scintigraphic findings. Computed tomography may be used to clarify the nature of a bony process. In addition to the CT findings already described, an additional finding is reported, consisting of the visualization of a small sequestrum. This finding has to be differentiated from the similar appearance in osteoid osteoma, intraosseous lipoma, fibrous dysplasia, and osteogenic sarcoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

1990
1990
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 8 publications
0
6
0
1
Order By: Relevance
“…Computed tomography (CT) has not been widely used in the evaluation of the diabetic foot. In 1979, Kuhn et al reported bone marrow density changes in osteomyelitis [16], and subsequent reports have described the detection of intraosseous gas and fatfluid levels as well as the visualization of sequestra in chronic osteomyelitis [13,20].…”
Section: Discussionmentioning
confidence: 97%
“…Computed tomography (CT) has not been widely used in the evaluation of the diabetic foot. In 1979, Kuhn et al reported bone marrow density changes in osteomyelitis [16], and subsequent reports have described the detection of intraosseous gas and fatfluid levels as well as the visualization of sequestra in chronic osteomyelitis [13,20].…”
Section: Discussionmentioning
confidence: 97%
“…Inside the osteomyelitis lesions there were colonies of bacteria within the metaphyseal capillary loops, so the present porcine model supports the theory that the pathogenesis of abscess formation in bones involves haematogenous spread. CT scanning has been reported as optimal for detection of small sequestra of devitalized bone tissue (Hernandez, 1985), which are reported to be present in paediatric osteomyelitis lesions after 10 days of infection (Steer and Carapetis, 2004). In the present study, devitalized bone tissue was seen as foci of increased opacity on the CT scans.…”
Section: Discussionmentioning
confidence: 69%
“…In these cases, the primary role of cross-sectional imaging is staging the infection. For example, CT is useful for surgical planning to identify a sequestrum or foreign body [56]. MRI can also help determine treatment in chronic osteomyelitis [57], by demonstrating non-drained abscesses, and by assessing the viability of the infected bone (by the presence or absence of enhancement after intravenous contrast administration).…”
Section: Destructionmentioning
confidence: 99%